Effect of warm-up with different weighted bats on normal baseball bat velocity - Montoya, B. S.; Brown, L. E.; Coburn, J. W.; Zinder, S. M. (The Journal of Strength and Conditioning Research, 2009)
Traditionally, baseball players have used a heavy bat for warm-up before competition. Because bat velocity is an essential component to hitting a baseball, and because players warm up differently, there is a need to investigate the best way to maximize post warm-up bat velocity. The purpose of this study was to determine the effects of warm-up with different weighted bats on normal baseball bat velocity. Nineteen recreational male baseball players (age, 24.5 ± 3.9 years; height, 181.1 ± 8.4 cm; body mass, 87.9 ± 18.4 kg) participated in this study. Three different randomized warm-up conditions were completed and analyzed for velocity and for their effect on post warm-up normal baseball bat velocity. Subjects were instructed to perform 5 maximal swings with each of 3 different weighted bats-light (LB = 9.6 oz), normal (NB = 31.5 oz), and heavy (HB = 55.2 oz)-followed by 30-second rest and then 5 swings of the NB. Analysis of variance revealed that warm-up velocity of the LB (63.57 ± 3.58 mph) was significantly (p < 0.05) faster than that of NB (51.25 ± 3.01 mph) and HB (41.79 ± 3.01 mph), whereas warm-up velocity of NB was also significantly faster than that of HB. For post warm-up, LB (52.29 ± 2.68 mph) and NB (50.60 ± 3.04 mph) produced significantly faster velocity of the normal bat than the HB (48.26 ± 2.98 mph). Warming up with 5 swings of a light or normal bat appears to increase post warm-up velocity of the normal bat when compared with warming up with a heavy bat after a rest period of 30 seconds. Within the bat weight spectrum of this study, it is suggested that when preparing to hit, 5 warm-up swings with either a light or normal bat will allow a player to achieve the greatest velocity of their normal bat.